KINERJA LINGKUNGAN, PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN DIVIDEND PAYOUT RATIO TERHADAP NILAI PERUSAHAAN - Putuhena, Hempry; Fauzan, M Rifkhi; Zalni, Zalni (Jurnal Cita Ekonomika, 2024)
Disclosure of information is not only limited to financial, non-financial aspects in the current era contain information that is essential for companies, especially to add value in the eyes of stakeholders. This research aims to see the influence of environmental performance, CSR disclosure, and dividend payout ratio on company value. The samples of consumer goods companies that can be observed during the 2019-2022 period are 12 companies. Testing using multiple linear regressions found that environmental performance, CSR disclosure, and dividend payout ratio had no effect on company value. Investors can see the determinants of company value, but this research did not find that the variables in this research could explain this, so there were 96.2% variables outside this research that could explain the relationship with company value.